Artificial Intelligence and Machine Learning for Business for Non-Engineers - Jones, Stephan; Groom, Frank M. (Milton : CRC Press LLC, 2019)
The next big area within the information and communication technology field is Artificial Intelligence (AI). The industry is moving to automate networks, cloud-based systems (e.g., Salesforce), databases (e.g., Oracle), AWS machine learning (e.g., Amazon Lex), and creating infrastructure that has the ability to adapt in real-time to changes and learn what to anticipate in the future. It is an area of technology that is coming faster and penetrating more areas of business than any other in our history. AI will be used from the C-suite to the distribution warehouse floor. Replete with case studies, this book provides a working knowledge of AI's current and future capabilities and the impact it will have on every business. It covers everything from healthcare to warehousing, banking, finance and education. It is essential reading for anyone involved in industry.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence; COMPUTERS / Machine Theory; BUSINESS & ECONOMICS / Information Management; COMPUTERS / Programming / Systems Analysis & Design